2012
DOI: 10.1080/11263504.2012.736421
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation management with glyphosate has little impact on understory species diversity or tree growth in a sub boreal spruce plantation – A case study

Abstract: In central British Columbia (BC), forest management practices have altered natural stand development pathways by controlling ''non commercial'' tree species and other competing species with the objective of maximizing crop tree growth. This potentially decreases overall diversity within the stand. We conducted a retrospective study on a 13-year-old stand to investigate the impacts of vegetation management with glyphosate on tree growth, species diversity and forest health in central BC. Results revealed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Species richness and the Shannon index did not differ between treated and untreated areas, indicating the small potential for impacts to plant community diversity resulting from operationally applied herbicide treatments, which is consistent with findings of several other studies [12,27,31]. Haeussler et al [13] report the potential for increases in species richness and other diversity indexes following herbicide treatment, which was also evident in our study when the single treatment applied in 2004 was compared to untreated areas.…”
Section: Discussionsupporting
confidence: 81%
“…Species richness and the Shannon index did not differ between treated and untreated areas, indicating the small potential for impacts to plant community diversity resulting from operationally applied herbicide treatments, which is consistent with findings of several other studies [12,27,31]. Haeussler et al [13] report the potential for increases in species richness and other diversity indexes following herbicide treatment, which was also evident in our study when the single treatment applied in 2004 was compared to untreated areas.…”
Section: Discussionsupporting
confidence: 81%
“…Considering potential savings with a targeted brushing program, a higher broadleaf component could be financially advantageous in addition to the noted biological benefits. In another study Hawkins et al (2012) reported that broadcast brushing did not remove all birches and suggested a move away from broadcast vegetation control to spot control, where warranted, could result in better tree growth, improved forest health and structural diversity. Therefore the inclusion of other broadleaf species in these complex processes may have more beneficial effects on spruce growth.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to unnecessary herbicide application costs for attaining a free growing standard and it may have a detrimental impact on ecosystems although a study by Hawkins et al (2012b) reported that herbicide application showed minimal or no impact on understorey vegetation diversity in central BC. From our investigation, birch densities up to 4,000 stems·ha -1 in 15-20 years old stands appear not to significantly influence spruce productivity in the northern BC interior.…”
Section: Management Implicationsmentioning
confidence: 99%